The Concept of Cognitive Space in the Context of Cognitive Securitology - O. V. Plebanek (Дискурс, 2024)
Introduction. The article discusses the conceptual foundations of a new field of knowledge – cognitive securitology.   The relevance of the study is due to the fact that the main means of cognitive warfare are modern digital technologies, while the object of influence of technical systems is mental systems, therefore there is a need to combine technical and humanitarian conceptual apparatus.   The purpose of the article is to clarify the concept of “cognitive space” and distinguish between the concepts of information and cognitive spaces.   Methodology and sources. One of the basic concepts of cognitive security is the concept of cognitive space, which has already been developed in linguistics, but due to the interdisciplinary nature of cognitive securitology needs to be clarified. Placing the category of cognitive space in the field of linguistic analysis narrows its content and does not make it possible to determine its semantic boundaries.   The novelty of the analysis of the category “cognitive space” lies in the fact that the conceptual analysis of the category of cognitive space is based on the concept of self-organizing systems and the structural-functional approach.   The concept of autopoiesis assumes that all elements and structures of the system, including cognitive ones, arise in order to ensure self-preservation, and the structural-functional approach allows us to determine the content and functions of the object.   Results and discussion. Information space and cognitive space are intersecting but not coinciding fields, differing in their domains, but having one common task – ensuring the stability of the social system.   Conclusion. The modern era is characterized by a global confrontation between civilizational systems and the transition of the confrontation into the phase of proxy wars, in which the main role is given to cognitive-psychological influence. Cognitive-psychological influence on the enemy is not only carried out at the preventive and preemptive stages of confrontation, but also often replaces other forms of war. Cognitive-psychological influence becomes possible and is carried out through the destruction of the cognitive space in which meanings and ideals that are specific to the social system function, which form goals and models of activity.